Long-term behavioral effects of prenatal stress in the Fmr1-knock-out mouse model for fragile X syndrome - Petroni, Valeria; Subashi, Enejda; Premoli, Marika; Memo, Maurizio; Lemaire, Valerie; Pietropaolo, Susanna (Frontiers in Cellular Neuroscience, 2022)
Fragile X Syndrome (FXS) is a major neurodevelopmental disorder and the most common monogenic cause of autism spectrum disorder (ASD). FXS is caused by a mutation in the X-linked FMR1 gene leading to the absence of the FMRP protein, inducing several behavioral deficits, including motor, emotional, cognitive and social abnormalities. Beside its clear genetic origins, FXS can be modulated by environmental factors, e.g., stress exposure: indeed the behavioral phenotype of FXS, as well as of ASD patients can be exacerbated by the repeated experience of stressful events, especially early in life. Here we investigated the long-term effects of prenatal exposure to unpredictable chronic stress on the behavioral phenotype of the Fmr1-knock-out (KO) mouse model for FXS and ASD. Mice were tested for FXS- and ASD-relevant behaviors first at adulthood (3 months) and then at aging (18 months), in order to assess the persistence and the potential time-related progression of the stress effects. Stress induced the selective emergence of behavioral deficits in Fmr1-KO mice that were evident in spatial memory only at aging. Stress also exerted several age-specific behavioral effects in mice of both genotypes: at adulthood it enhanced anxiety levels and reduced social interaction, while at aging it enhanced locomotor activity, reduced thecomplexity of ultrasonic calls. Our findings underline the relevance of gene-environment interactions in mouse models of neurodevelopmental syndromes and highlight the long-term behavioral impact of prenatal stress in laboratory mice.